"Best invention, second to the dishwasher": Vibrators and sexual pleasure. (September 2020) - Waskul, Dennis; Anklan, Michelle
This study examines how people learn about vibrators, their attitudes toward them, fears or hesitations about acquiring and/or using one, and the significance of vibrators to participants' sexualities. Based on 78–147 responses to an online open-ended survey, participants report: primarily learning about vibrators from media and peers; their interpretations of media representations of vibrators are juxtaposed as both a tool for great pleasure and a shameful taboo; that vibrators are often perceived as a "dick substitute" for women who are unsuccessful at satisfying partnered heterosex; their initial purchase of a vibrator was inhibited by cost, fears that others would discover that they owned one, and ignorance about the technology, how their body would respond, and what they knew about their body; the majority of participants use vibrators both alone and in partnered sex; and the vast majority of participants who do not own a vibrator report that they would like to and anticipate purchasing one in the future. These findings illustrate the increasing normativity of vibrators that is justified by post-feminist ideals, while also repeatedly illustrating the continued feelings of shame and embarrassment, and fears of stigmatization.